Análisis de los indicadores financieros en las cooperativas de ahorro y crédito Segmentación 3, de la provincia de Tungurahua, de la ciudad de Ambato 2021 - Aimacaña Llumiquinga, Viviana Lisbeth (2023)
The objective of this work is to analyze the financial indicators in the Savings and Credit Cooperatives segment 3 of the Tungurahua province of the city of Ambato 2021. This research presents a theoretical foundation that covers the variable of the object of study. The research methodology contemplates a quantitative approach, in the same way the type of research that was carried out is indicated, four COAC'S from the city of Ambato corresponding to segment 3 of the classification of the Superintendency of Popular and Solidarity Economy were considered. , COAC Coorambato Ltda., COAC Campesina Coopac, COAC “Acción Tungurahua” and COAC “Credi Ya” Ltda.